2022
DOI: 10.1002/adma.202109547
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured, Fluid‐Bicontinuous Gels for Continuous‐Flow Liquid–Liquid Extraction

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.202109547. Fluid-bicontinuous gels are unique materials that allow two distinct fluids to interact through a percolating, rigid scaffold. Current restrictions for their use are the large fluid-channel sizes (>5 µm), limiting the fluid-fluid interaction surface-area, and the inability to flow liquids through the channels. In this work a scalable synthesis route of nanoparticle stabilized fluid-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…4,15,16 In comparison to thermal quench-based methods, chemical quenching allows access to much higher interfacial tensions as phase separation proceeds. 17 However, the flow generated by co-solvent removal has a significant impact on the resulting bijels' structures. In solvent transfer-induced phase separation (STRIPS), the partitioning of co-solvent to the outer liquid phase induces a strong flow that drives the formation of anisotropic domains aligned in the direction of the co-solvent flux.…”
Section: Materials Horizonsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,15,16 In comparison to thermal quench-based methods, chemical quenching allows access to much higher interfacial tensions as phase separation proceeds. 17 However, the flow generated by co-solvent removal has a significant impact on the resulting bijels' structures. In solvent transfer-induced phase separation (STRIPS), the partitioning of co-solvent to the outer liquid phase induces a strong flow that drives the formation of anisotropic domains aligned in the direction of the co-solvent flux.…”
Section: Materials Horizonsmentioning
confidence: 99%
“…The ability to form bijels with uniform, sub-micrometer domains would enable their utilization in reactive separation, fluid-fluid extraction, flow batteries, fabrication of anti-cracking composite matrix 19 as well as optics and photonics. For liquid phase reaction and extraction, the large surface area facilitates reaction and mass transfer between two phases 17,20,21 whereas the uniform channels provide homogeneous flow/solute distributions [22][23][24] essential, for example, to flow battery function. For photonics, recent simulation results have proposed that spinodal structures exhibit hyperuniformity 25 making bijel-templated materials potentially useful for designing photonic band gaps.…”
Section: Materials Horizonsmentioning
confidence: 99%
“…It shall be noted that these equilibrium compositions may not be fully representative for the nonequilibrium process during STrIPS. Nevertheless, our recent work showed that equilibrium compositions can model the nonequilibrium interfacial tension evolution during STrIPS . Therefore, we prepare equilibrium mixtures with compositions in the middle of the tie-lines (ensuring equal volumes of BDA- and water-rich phases) given by points 1, 2, 3, and 4 in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, our recent work showed that equilibrium compositions can model the nonequilibrium interfacial tension evolution during STrIPS. 22 Therefore, we prepare equilibrium mixtures with compositions in the middle of the tie-lines (ensuring equal volumes of BDA-and water-rich phases) given by points 1, 2, 3, and 4 in Figure 6b. The mixtures contain the same Ludox TMA and CTA + concentrations as the compositions used to make the fibers.…”
Section: Structure Formation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation